Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw Berbantuan E-Modul Terhadap Berpikir Kritis, Kemandirian Belajar, dan Hasil Belajar Materi Ekosistem Kelas V - Tri Susilowati (Perkumpulan Kualitama Edukatika Indonesia, 2022)
The problem is the independence of learning and the learning outcomes of class V students, who are still low. The low independence and learning outcomes are caused partly because the teacher only using conventional learning methods, namely the lecture method. The learning going on so far has been less able to develop students' critical thinking in class V at SDN Brambang. Low critical thinking has an impact on independence and student learning outcomes. Therefore, a way is needed to increase student independence and learning outcomes. This study aims to determine the effect of the Jigsaw cooperative learning model assisted by the E-Module on critical thinking, independent learning, and student learning outcomes on ecosystem material for class V. The research method used is Quasi Experiment with Posttest Control Group Design. The research population was VB class students as the control class and VA class students as the experimental class. The data collection technique used was a critical thinking questionnaire, and a learning independence questionnaire declared feasible for research and learning achievement test questions.